2003
DOI: 10.1093/jjco/hyg053
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of the Simultaneous Integrated Boost (SIB) Method for Malignant Gliomas Using Intensity-modulated Radiotherapy (IMRT)

Abstract: The treatment of 70 Gy/28 fr/daily 2.5 Gy to the GTV and 56 Gy/28 fr/daily 2.0 Gy to the CTV-a was feasible both physically and clinically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…We have already reported the details of the target volume delineation in this clinical trial, in which the contouring of PTV-G and PTV-a was graphically demonstrated. 6,12 Treatment planning A commercial treatment-planning system (Cadplan Helios ver.6.01; Varian Associates, Palo Alto, CA, USA) was used. The IMRT beam arrangements consisted of fi ve coplanar beams.…”
Section: Target Volume Delineationmentioning
confidence: 99%
See 2 more Smart Citations
“…We have already reported the details of the target volume delineation in this clinical trial, in which the contouring of PTV-G and PTV-a was graphically demonstrated. 6,12 Treatment planning A commercial treatment-planning system (Cadplan Helios ver.6.01; Varian Associates, Palo Alto, CA, USA) was used. The IMRT beam arrangements consisted of fi ve coplanar beams.…”
Section: Target Volume Delineationmentioning
confidence: 99%
“…Details of the quality assurances (QA) in the present study have been described in our previous report. 6 Chemotherapy Eleven of the 13 patients received one or two courses of nimustine hydrochloride (ACNU) (100 mg/m 2 ) and vincristine (1.2 mg/body) and interferon-β (3 × 10 6 units) three times weekly during the radiotherapy. Adjuvant chemotherapy, ACNU (100 mg/m 2 ) and vincristine (1.2 mg/body), was repeated every 6 weeks and interferon-β was repeated every 2 weeks.…”
Section: Treatment Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Mohan et al [4] introduced the concept of SIB IMRT: Advantageous technique in terms of better conformity to target, shorter treatment time, better dose hotspot control and reduced exposure of radiations to Organs at Risk (OARs) such as parotids, spinal cords, optic nerve, optic chaisma, brain stem, and oral cavity [3][4]. This technique is specifically found useful for head and neck carcinoma due to histologically heterogeneous nature of tumor and low dose radiation tolerance to normal surrounding tissues [5][6]. To achieve local control of disease, high dose of radiation in the range of 70 Gy is required in the treatment of head and neck cancer [1].…”
Section: Introductionmentioning
confidence: 99%
“…To verify leaf motion of each beam or specific patient's plans, various quality assurance tests were conducted [8,9]. Once the VMAT plan was developed and approved, CT simulation datasets were imported into the ExacTrac® X-ray 6D system (BrainLab AG, Feldkirchen, Germany) for 2D/3D registration using digital reconstructed radiographs (DRRs) of 2D oblique images to the planning CT images [10].…”
mentioning
confidence: 99%